(3OjhGf GdeJfHjs - (3CMeO Hf GdMSjf Hf GdMSf Hf YHO GdUeO Hf GdLYaj Gdchaj GdeJfHj, CHh GdWjH, J (B354 (3g` s
(3ChdgG (B:s
(3hdO CHhGdWjH GdeJfHj HGdchaI SfI KdGK hKdGKeGFI hbGd GdTYQ UHjkG aef Chd eG bGdg(B: (3CHcj Gdghi CUaG jhe Gdfhi HOfj haQb GdgLQ Hjf GdLaf hGdhSf s
(3BNQgG (B:s
(3faSj JUZQ faS GdOgQ ef cHQ dgG fgj cgdg aj Sf CeQOg gPG BNQ TYQ CHj GdWjH GdeJfHj ef ehdOg Edi ebJdg QMeg Gddg s
(3HgG ChQGb aj ChdgG hhSWgG hbHd BNQgG ocJHJ HNW eZGjQ eJCNQs
(3hQO CjVoG JMJ Qbe (B873(3, (B917(3, (B2191(3, (B2195s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
Keywords: (3GdCOHs